Common and spatial drivers in regional business cycles - Michael J. Artis; Christian Dreger; Konstantin Arkadievich Kholodilin (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
We examine real business cycle convergence for 41 euro area regions and 48 US states. Results obtained by a panel model with spatial correlation indicate that the relevance of common business cycle factors is rather stable over the past two decades in the euro area and the US. Ongoing business cycle convergence often detected in a country data is not confirmed at the regional level. The degree of synchronization across the euro area is similar to that to be found for the US states. Thus, the lack of convergence does not seem to be an impediment to a common monetary policy.
Keywords: E32; C51; E37; 330; Business cycle convergence; spatial correlation; spatial panel model; Regionaler Konjunkturzyklus; Entwicklungskonvergenz; Korrelation; Panel; Schätzung; EU-Staaten; USA